Guard lines conformal slotted antenna array for multiband application - Brajlata Chauhan; Suresh Chandra Gupta; Sandip Vijay (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
This work investigated a miniaturized slotted conformal antenna array for multiband application. Three guard lines are incorporated to the side of main patch and top of main patch to reduce surface current for planner surface and observe the effect of guard line due to which it resonate at three frequencies in X band and Ku band to be useful for multiband. A rectangular slot is etched at center of patches to increase the current path for wide band application. A quarter wavelength feeding network is used with good agreement of impedance matching. The main lobe width and direction shows through the radiation pattern which remains stable even it is significantly curved. This structure is wrapped around a cylinder with a diameter of 41.4 mm in the circumferential direction. It is observed that the planner antenna array operating at 8.4 GHz, 11.2 GHz &18.2 GHz with a return loss of -20 dB to -45 dB with fractional BW of 25% at 3rd frequency range and the directivity from 3.4 dBi-6.8 dBi. By doing some alteration in dimensions for the conformal antenna producing fractional BW of 20% and the directivity 5.5 to 9.1 dBi at resonating frequencies of 8.4 GHz, 11.4 GHz, and 17.5 GHz. This proposed array is simulated on CST software.